2012
DOI: 10.1371/journal.pone.0047764
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Profile Associated with the Abnormality of Bone Marrow Mesenchymal Stem Cells in Aplastic Anemia

Abstract: Aplastic anemia (AA) is generally considered as an immune-mediated bone marrow failure syndrome with defective hematopoietic stem cells (HSCs) and marrow microenvironment. Previous studies have demonstrated the defective HSCs and aberrant T cellular-immunity in AA using a microarray approach. However, little is known about the overall specialty of bone marrow mesenchymal stem cells (BM-MSCs). In the present study, we comprehensively compared the biological features and gene expression profile of BM-MSCs betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
76
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 26 publications
3
76
1
Order By: Relevance
“…In fact, AA patients have a hypocellular BM which is "physiologically" replaced by fatty BM, likely of mesenchymal origin, further supporting a potential contribution of the BM microenvironment to the pathogenesis of AA. 41 MSC have robust immunomodulatory and anti-inflammatory properties [11][12][13] and are an essential component of the BM hematopoietic microenvironment, which regulates the homeostasis of hematopoiesis through the production and secretion of cytokines and extracellular matrix molecules.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, AA patients have a hypocellular BM which is "physiologically" replaced by fatty BM, likely of mesenchymal origin, further supporting a potential contribution of the BM microenvironment to the pathogenesis of AA. 41 MSC have robust immunomodulatory and anti-inflammatory properties [11][12][13] and are an essential component of the BM hematopoietic microenvironment, which regulates the homeostasis of hematopoiesis through the production and secretion of cytokines and extracellular matrix molecules.…”
Section: Discussionmentioning
confidence: 99%
“…8,[41][42][43][44][45][46][47][48] These studies mainly claim that AA BM-MSC have aberrant morphology, impaired adipogenic and osteogenic potential, changes in gene expression, and a reduced ability to support hematopoiesis in vitro. However, to the best of our knowledge, no study so far has prospectively addressed in depth the ability of AA BM-MSC to maintain hematopoietic homeostasis and progenitor function in vitro, their in vivo repopulating function in xenotransplant models, or the immunosuppressive and anti-inflammatory properties on these cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome-wide gene expression cDNA microarray is a powerful technique used to investigate the pathophysiology of a variety of diseases, including tumors (28-30), immune-mediated diseases (31,32) and inflammatory diseases (33)(34)(35). Using microarray, Chang et al revealed that genes characteristically expressed by tumor-associated macrophages were upregulated by DcR3 (30).…”
Section: Discussionmentioning
confidence: 99%